A new application of passive samplers as indicators of in-situ biodegradation processes. (December 2016) - Belles, Angel; Alary, Claire; Criquet, Justine; Billon, Gabriel
Abstract: In this paper, a method for evaluating the in-situ degradation of nitro polycyclic aromatic hydrocarbons (nitro-PAH) in sediments is presented. The methodology is adapted from the passive sampler technique, which commonly uses the dissipation rate of labeled compounds loaded in passive sampler devices to sense the environmental conditions of exposure. In the present study, polymeric passive samplers (made of polyethylene strips) loaded with a set of labeled polycyclic aromatic hydrocarbons (PAH) and nitro-PAH were immersed in sediments (in field and laboratory conditions) to track the degradation processes. This approach is theoretically based on the fact that a degradation process induces a steeper concentration gradient of the labeled compounds in the surrounding sediment, thereby increasing their compound dissipation rates compared with their dissipation in abiotic conditions. Postulating that the degradation magnitude is the same for the labeled compounds loaded in polyethylene strips and for their native homologs that are potentially present in the sediment, the field degradation of 3 nitro-PAH (2-nitro-fluorene, 1-nitro-pyrene, 6-nitro-chrysene) was semi-quantitatively analyzed using the developed method. Graphical abstract: Highlights: Passive samplers were used with tracer compounds to analyze degradation processes. Degradation increases the dissipation of labeled nitro-PAH from passive samplers. In-situ nitro-PAH degradation was demonstrated in field sediments.